Role of dielectric properties in terahertz field transmission - Seo, Minah; Lee, Joong Wook; Kim, Hwi (AMER INST PHYSICS, 2015)
We compare the field transmission characteristics of a freestanding perforated metal film (as a conducsssstor) and a polymethylmethacrylate-graphite composite film (as an absorber) in the terahertz frequency range. The role of dielectric properties of the materials and the contribution of surface waves toward enhanced transmission with periodic and random hole arrays are discussed. Periodic subwavelength hole arrays in metal films do support enhanced terahertz field transmission whereas random arrays do not. In contrast, neither periodic nor random arrays of subwavelength holes punctured in dielectric absorbers support such transmission. Notably, even a dielectric absorber with large holes, which is sufficiently larger than subwavelength holes, can result in features in transmission due to the shape resonance, but the effect is very small. (C) 2015 AIP Publishing LLC.
Keywords: SURFACES; ARRAYS; TRANSMITTANCE; METAMATERIALS; PLASMONS; FILMS